Optimization of radiation protection in radionuclide therapy: Proposals for developing quality assurance programs - A. V. Likhacheva; A. V. Vodovatov; L. A. Chipiga (Радиационная гигиена)
In order to ensure a high-quality and safe therapeutic process in radionuclide therapy, it is not sufficient to rely solely on safety monitoring within the framework of production control. Measures must be implemented within a quality assurance system as established in the quality assurance program. The purpose of this work is to define the requirements for quality assurance program in radionuclide therapy in terms of the ensuring radiation safety for patients, staff, the public, and the environment. The work discusses approaches to developing a quality assurance program in radionuclide therapy as a tool for optimizing radiation protection for patients, medical staff, and the public. The proposed structure of the quality assurance program covers all stages of radionuclide therapy – from patient identification and radiopharmaceutical quality control to the evaluation of therapeutic efficacy and safety at all levels. Particular attention is given to the need for equipment monitoring, imaging parameter control, management of biological waste, patient instruction upon discharge, as well as dosimetry-guided radionuclide therapy planning aimed at optimizing patient radiation protection. The quality assurance program in radionuclide therapy is proposed as a foundation for building a standardized, safe, and effective quality assurance system aligned with international practices, with a primary focus on personalized approaches to the planning and delivery of radionuclide therapy.